Ultrasound correlation of transcerebellar diameter with last menstrual period for gestational age in second and third trimester of pregnancy (Journal of Kathmandu Medical College, 2022)
Background: Foetal biometry is useful modality in assessment of gestational age (GA) for good obstetric outcome. Objectives: To compare ultrasonographic measurement of transverse cerebellar diameter (TCD) with other previously established foetal ultrasound biometric parameters. Methods: An analytical cross-sectional study was conducted from August 2020 to February 2021 in Department of Radiology at Kathmandu Medical College after ethical clearance. Convenience sampling technique was utilised to include all pregnant women in second and third trimester with known last menstrual period (LMP). Written informed consent was taken from those willing to participate. Congenital malformations, multiple pregnancies, irregular menstrual cycle, and maternal illness were excluded. Data were entered and analysed by using SPSS v.22. Descriptive statistics like mean, standard deviation, and percent were used. Inferential statistics (t- test and Pearson correlation) was also used to see the correlation between different variables. Results: Among 100 participants who participated in the study, 63 (63%) were primigravida with singleton pregnancy without any congenital anomalies. The mean foetal heart rate was 144.9 ± 13.6. The mean GA based on LMP, TCD, and other parameters were 30.86 ± 7.76 weeks, 31.07 ± 8.45 weeks, and 29.75 ± 6.61 weeks respectively. In 15-28 weeks, all parameters had nearly equal r-values. Among all, TCD revealed highest correlation (0.888). In 29-40 weeks, there was considerable difference in r-values. The second most accurate correlation was seen with head circumference (r = 0.874). Conclusion: TCD being stable parameter not affected by foetal growth status maybe preferred over other parameters in estimating foetal gestational age.